Then they came for me : a family's story of love, captivity, and survival - Bahari, Maziar (Random House, 2010)
A riveting, heart-wrenching memoir of Maziar Bahari's brutal interrogation in Iran's most notorious prison, offering insight into Iran's turbulent recent past and uncertain future.